Esophageal secondary peristalsis following acid infusion and chemical clearance correlate with mucosal integrity and acid sensitivity in GERD patients - Ming-Wun Wong; Jui-Sheng Hung; Wei-Yi Lei; Tso-Tsai Liu; Chih-Hsun Yi; Shu-Wei Liang; Chandra Prakash Gyawali; Jen-Hung Wang; Chien-Lin Chen (Therapeutic Advances in Gastroenterology, 2023)
Background: Acid sensitivity can be altered in patients with gastroesophageal reflux disease (GERD). Secondary peristalsis helps clear gastro-esophageal refluxate and residual ingested food bolus. Objectives: The aim of this study was to investigate the associations among acid sensitivity, esophageal mucosal integrity, chemical clearance, and secondary peristalsis before and after esophageal acid infusion. Design: This was an investigator-initiated, prospective, cross-sectional study. Methods: Adult reflux patients underwent high resolution manometry and 24 h impedance-pH monitoring off acid suppression to identify GERD phenotypes, including non-erosive reflux disease (NERD), reflux hypersensitivity (RH), and functional heartburn (FH). Secondary peristalsis was assessed using five rapid 20 mL air injections into the esophagus before and after infusion of hydrochloric acid (0.1 N) into the mid-esophagus. Conventional acid infusion parameters recorded included lag time, intensity rating, and sensitivity score. Chemical clearance was evaluated using the post-reflux swallow-induced peristaltic wave (PSPW), and mucosal integrity was assessed by the mean nocturnal baseline impedance (MNBI) derived from impedance-pH monitoring. Results: A total of 88 patients (age 21–64 years, 62.5% women) completed the study including 12 patients with NERD, 45 with RH, and 31 with FH. There was no significant difference in acid infusion parameters between patients with NERD, RH, and FH. Upon acid infusion, patients who exhibited successful secondary peristalsis had longer lag time, higher MNBI, and shorter bolus contact time than those without secondary peristalsis. Meanwhile, patients with intact PSPW demonstrated significantly higher intensity ratings in response to acid perfusion and higher MNBI than those with impaired PSPW. The lag time correlated positively with MNBI ( r  = 0.285; p  = 0.007). Conclusion: In conclusion, the protective effect of esophageal secondary peristalsis and chemical clearance on esophageal mucosal integrity was demonstrated. Concerning acid sensitivity, longer lag time in patients with intact secondary peristalsis may be attributed to better esophageal mucosal integrity, while stronger intensity ratings may have a greater tendency to induce PSPW and protect esophageal mucosal integrity.